Human and cervid osseous materials used for barbed point manufacture in Mesolithic Doggerland. (February 2021) - Dekker, Joannes; Sinet-Mathiot, Virginie; Spithoven, Merel; Smit, Bjørn; Wilcke, Arndt; Welker, Frido; Verpoorte, Alexander; Soressi, Marie
Graphical abstract: Highlights: ZooMS analysis was performed on ten barbed points from the Dutch North Sea coast. We combine this with direct 14 C dating, δ 13 C and δ 15 N analysis. Unexpectedly, two barbed points were manufactured from human bone. The other barbed points derive from red deer and/or elk bones and antler. The 14 C age of the points range from 9.5 to 7.3 ka 14 C BP. Abstract: Barbed bone points originally deposited in Doggerland are regularly collected from the shores of the Netherlands. Their typology and direct 14 C dating suggest they are of Mesolithic age. However, the species of which the barbed points were made cannot be identified based on morphological criteria. The bones used to produce the barbed points have been intensively modified during manufacture, use, and post-depositional processes. Here, we taxonomically assess ten barbed points found on the Dutch shore using mass spectrometry and collagen peptide mass fingerprinting alongside newly acquired 14 C ages and δ 13 C and δ 15 N measurements. Our results demonstrate a sufficient preservation of unmodified collagen for mass spectrometry-based taxonomic identifications of bone and antler artefacts which have been preserved in marine environments since the beginning of the Holocene. We show that Homo sapiens bones as well as Cervus elaphus bones and antlers were transformed into barbed points. The 14 C dating of nine barbed points yielded uncalibrated ages between 9.5 and 7.3 ka 14 C BP. The δ 13 C and δ 15 N values of the seven cervid bone points fall within the range of herbivores, recovered from the North Sea, whereas the two human bone points indicate a freshwater and/or terrestrial fauna diet. The wide-scale application of ZooMS is a critical next step towards revealing the selection of species for osseous-tool manufacture in the context of Mesolithic Doggerland, but also further afield. The selection of Cervus elaphus and human bone for manufacturing barbed points in Mesolithic Doggerland is unlikely to have been opportunistic and instead seems to be strategic in nature. Further, the occurrence of Homo sapiens and Cervus elaphus bones in our random and limited dataset suggests that the selection of these species for barbed point production was non-random and subject to specific criteria. By highlighting the transformation of human bones into barbed points – possibly used as weapons – our study provides additional evidence for the complex manipulation of human remains during the Mesolithic, now also evidenced in Doggerland.